PENGARUH BAURAN PEMASARAN ECERAN (RETAIL MARKETING MIX) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI MATAHARI DEPARTMENT STORE BANGKALAN PLAZA - ADITYA P, FAJAR (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
The development of retail in Indonesia is growing rapidly reveals that’s consumer’s purchase power is getting higher. In the middle of 2012, Matahari Department Store as one of the largest Department Store retail in Indonesia has opened its 108th outlet’s in Bangkalan, East Java. As the newest outlet, many strategies have to be applied to attract that consumer’s that would like to visit and make some purchase transactions. One of those strategies is the retail mix strategies which consists of location, service, product, price, store atmosphere, employees, and promotions. This research is quantitative research by using survey approach which tries to determine the influence of retail mix on costumer’s purchase decisions in Matahari Department Store Bangkalan Plaza. The result of this research showed that the simultaneous and partial independents variable’s which consists of Location (X1), Service (X2), Product (X3), Price (X4), Store Atmosphere (X5), Employees (X6),and Promotions (X7) have no effect on the dependent variable for the costumers purchases (Y). Adjusted R Square Value = 0,028 means 2,80% of the costumer’s purchase can be explained by the independent variable in this research and as the amount over 97,20% which affected by pther variables outside this research model. Keyword : Retailing Mix , Costumers Purchase